Trap-assisted tunneling mechanism of Zirconium Oxynitride (ZrON) thin film on Silicon Carbide / Nicklaane Krishnamoorthy - Nicklaane, Krishnamoorthy (2020)
This research is a study on the possibilities of trap-assisted tunneling conduction mechanism in Zirconium Oxynitride (ZrON) after Zirconium (Zr) with thickness 5nm was sputtered on Silicon Carbide (SiC) substrate which then underwent simultaneous nitridation and oxidation in Nitrous Oxide (N2O) for 15 minutes in 4 different ambient temperatures of 400°C, 500°C, 700⁰C, 900°C. Electrical properties of the samples were then characterized by fabricating Al-gate MOS capacitors onto the film surface. Of all 4 samples, sample that was oxidized/nitrided at 500°C demonstrated to have the highest dielectric breakdown (EB) of 5.05 MV/cm and lowest EB was by sample that was oxidized/nitrided at 900°C. The 1st step breakdown in J-E curve by samples oxidized/nitrided at 500°C, 700°C and 900°C were minor but there were also 2nd step breakdown and this explains that those samples could be a trap assisted tunneling (TAT) conduction mechanism. From graph of ln (JE) vs 1/E, the intercept and slope from the regression line have given the value for lowest trap density and highest trap energy at -35.8 x 1021 cm-3 and 5.92eV, respectively.